2016
DOI: 10.1007/s13346-016-0292-0
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystal for ocular drug delivery: hope or hype

Abstract: The complexity of the structure and nature of the eye emanates a challenge for drug delivery to formulation scientists. Lower bioavailability concern of conventional ocular formulation provokes the interest of researchers in the development of novel drug delivery system. Nanotechnology-based formulations have been extensively investigated and found propitious in improving bioavailability of drugs by overcoming ocular barriers prevailing in the eye. The advent of nanocrystals helped in combating the problem of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 97 publications
1
44
0
1
Order By: Relevance
“…If a drug can penetrate the full thickness of cornea and reach the anterior chamber in high concentration, then further diffusion into the posterior chamber should occur easily. Recently, it was suggested that this long challenging problem could be overcome with the use of nano-based drug carriers56. Several recent reports of successful intraocular drugs or gene deliveries by various nanoparticles further increased such expectations18192021222324.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If a drug can penetrate the full thickness of cornea and reach the anterior chamber in high concentration, then further diffusion into the posterior chamber should occur easily. Recently, it was suggested that this long challenging problem could be overcome with the use of nano-based drug carriers56. Several recent reports of successful intraocular drugs or gene deliveries by various nanoparticles further increased such expectations18192021222324.…”
Section: Discussionmentioning
confidence: 99%
“…To enhance ocular drug penetration, nanoparticle based drug delivery systems have been intensively investigated with promising results456. Amorphous silica nanoparticles (SiNPs) are some of the most promising nanoparticle systems for ocular drug delivery.…”
mentioning
confidence: 99%
“…In addition, nano‐crystals are beneficial for long time retainment on eye surface. Nano‐crystals can be retained in the cul‐de‐sac and its large surface area allows long‐term adhesion to the eye surface …”
Section: Introductionmentioning
confidence: 99%
“…Despite the distinct advantages of local therapies, a highly efficient ophthalmic drug delivery approach remains one of the most challenging tasks for pharmaceutical formulators and scientists because of various physiological barriers (Figure ) . In the anterior segment of the eye, the corneal‐aqueous humor barrier, physiological blinking, and tear drainage are dominant factors for rapid drug clearance after topical instillation .…”
Section: Introductionmentioning
confidence: 99%